An investigation of various applications and related challenges in cloud computing. (2022) - Pallathadka, Harikumar; Sajja, Guna Sekhar; Phasinam, Khongdet; Ritonga, Mahyudin; Naved, Mohd; Bansal, Rajni; Quiñonez-Choquecota, Jose
Abstract: Cloud computing is one of the most powerful inventions that has grabbed the curiosity of technologists all around the world. Cloud computing has many advantages, but it also has a slew of security risks that no organization can afford to ignore. Cloud computing offers several advantages and appealing characteristics to attract company suppliers, including no up-front investment, decreased operational expenses, highly scalable, simple access, lowering business risks, and maintenance costs. Cloud computing is useful in most of the real world areas. Most educational institutions throughout the world use learning management systems, content management systems, virtual networks, and virtual machines to facilitate student learning. Similarly, in agriculture, cloud computing aids with crop and soil information tracking, e-commerce, logistics, farmer data, and expert consultation. This article discusses cloud computing uses and functions in education and agriculture. This article also presents various issues and challenges related to cloud computing.